DOES ENTREPRENEURSHIP DICTATE THE PROFITABILITY GROWTH OF FIRMS? (EVIDENCE FROM FRANCE) - Morched, Salim; Jarboui, Anis (APPS Publications, 2021)
Nowadays, entrepreneurship is greatly influenced by several aspects, including globalization, the increase of economic, industrial upgrade, incorporation of culture, and many other exchanges. Focusing on entrepreneurship, the trend of international companies' development is environmental dynamism, financial capital accessing, and professional codes. The influence of corporate entrepreneurship on the growth of firms‘ profits is the main interest of this paper. Thirty-seven French firms are subject to examination during the four years, starting from 2014 until 2018. With the help of STATA 13.0 software, data collected was analyzed by using multiple regression analysis. The findings show that entrepreneurship and environmental and financial capital taking dimensions undergo a considerably favorable impact on the progress of profitableness of firms. This assists in the research area of entrepreneurship in underdeveloped countries and boosts the effects of entrepreneurial aspects on the accomplishment and the development of firms.